A New large Mesh Trawl for Demersal Fishery - KUNJIPALU, K K; KUTTAPPAN, A C; MATHAI, P GEORGE (Fishery Technology, 2017)
A new large mesh demersal trawl of 32 m head rope length is found more efficient for the exploitation of demersal fishes off Vera val. Increased catch with a proportionate increase of demersal fishes was obtained when compared to a standard bottom trawl of 32 m head rope length with small meshes, suggesting the possibility of increasing the mesh size of trawl nets in the forepart. This increases the niouth area of net which enhances the fishing power by covering a large area per tow. The net is simple in construction, easy to repair and maintain and fewer in the number of meshes.